Menganalisis Sejarah Kantor Pos Medan - Pristi Suhendro Lukitoyo; Muhammad Arif Fauzi; Oktavina Sijabat; Rahel Exclesya; Yesi Astasia (CV. Rayyan Dwi Bharata, 2026)
1.What is the background of the establishment of the Medan Post Office 2. Who is the founder of the Medan Post Office 3. Where is the Medan Post Office located 4. When was the Medan Post Office founded 5. Why was the Medan Post Office founded 6. What are the roles and functions of the Medan Post Office in providing services. Research Objectives As befits writing, it must have goals and benefits. The purpose of writing this paper is to fulfill the assignment from Mrs. Dr. Rosmaida Sinaga, M.Hum as a Lecturer for the course “Indonesian History of the Colonial Period” besides that, she also answered from the problem formulations that had been made. The benefits of writing are to add to the author’s insight regarding “The History of the Medan Post Office in the Dutch Colonial Period (1911-1942)”. The research method used by the author is the historical method or historical method. Heuristics is a step in the work of historians to find and collect historical sources or evidence. The Medan post office building which was first established by the Dutch colonial government during the leadership of Resident J. Ballot which is located around Medan Merdeka Square (formerly Esplanade Field) was built by an architect named Ir. S. Snuyf from BOW (Burgelijke Openbare Werken) or the Dutch East Indies government public works service for Indonesia at that time. From the beginning of its establishment, the Medan post office had a function, namely as a place or means of sending existing letters or goods. Where in carrying out its functions in sending letters using postcards and others by using postage as a sign of settlement.